A convergent total synthesis of ouabagenin. Issue 6 (16th April 2015) - Mukai, Ken; Kasuya, Satoshi; Nakagawa, Yuki; Urabe, Daisuke; Inoue, Masayuki
Abstract : A convergent total synthesis of ouabagenin, an aglycon of cardenolide glycoside ouabain, was achieved by assembly of the AB-ring, D-ring and butenolide moieties. Abstract : A convergent total synthesis of ouabagenin, an aglycon of cardenolide glycoside ouabain, was achieved by assembly of the AB-ring, D-ring and butenolide moieties. The multiply oxygenated cis -decalin structure of the AB-ring was constructed from ( R )-perillaldehyde through the Diels–Alder reaction and sequential oxidations. The intermolecular acetal formation of the AB-ring and D-ring fragments, and combination of the intramolecular radical and aldol reactions, assembled the requisite steroidal skeleton in a stereoselective fashion. Finally, stereoselective installation of the C17-butenolide via the Stille coupling and hydrogenation led to ouabagenin.